Chemical Properties of Red Rose (Rosa Indica L.) Herbal Tea with Variations of Temperature and Drying Time - Titisari Juwitaningtyas; Amy Amalia (Universitas Ahmad Dahlan, 2022)
Red roses (Rosa Indica L.) are ornamental plants containing functional compounds that are good for health, such as antioxidants, vitamin C, and polyphenols. Due to the functional compounds in red roses, they can be processed into herbal teas. This study aims to determine the chemical nature of red rose herbal tea with variations in temperature and drying time. This study was designed using a Completely Randomized Design (CRD) consisting of two treatment factors: drying temperature T1= 50 oC, T2= 60 oC, T3= 70 oC, and drying time S1=2 hours, and S2=3 hours. The parameters measured were the water content in dried flowers, while the antioxidant activity and total phenol were carried out in steeping dried flowers. The study results were processed using a two-way ANOVA (analysis of variance). The results showed that temperature and drying time significantly affected moisture content, antioxidant activity, and total phenol of red rose herbal tea. Red rose herbal tea produced the lowest water content of 4.55% in sample T3S2, and the highest antioxidant activity was 54.01% in sample T1S1. The highest total phenol was 11.45 mg GAE/g in sample T1S1.